Effect of Core Topology on Vibro-acoustic Characteristics of Truss Core Sandwich Panels. (2016) - Arunkumar, M.P.; Pitchaimani, Jeyaraj; Gangadharan, K.V.; Leninbabu, M.C.
Abstract: This paper presents numerical simulation studies on effect of core topology on vibro–acoustic behaviour of truss core sandwich panels with metal facings. Free and forced vibration responses of the panels are obtained using finite element method based on the equivalent 2-dimensional models. Sound radiation characteristics of the panel are obtained using Rayleigh integral. It is found that influence of nature of core topology on sound radiation is significant in lower frequencies. It is observed that compared to trapezoidal and rectangular core, triangular core is more suitable for low frequency application and also it radiates less sound compare to trapezoidal and rectangular core.